Predicting the performance of oxidation catalysts using descriptor models. Issue 1 (19th August 2015) - Madaan, Neetika; Shiju, N. Raveendran; Rothenberg, Gadi
Abstract : Mix & match: we show that combining simple heuristic models with experimental validation is an effective method for optimising supported mixed oxide catalysts. Abstract : Practical solutions in catalysis require catalysts that are active and stable. Mixed metal oxides are robust materials, and as such are often used as industrial catalysts. The problem is that predicting their performance a priori is difficult. Following our work on simple descriptors for supported metals based on Slater-type orbitals, we show here that a similar paradigm holds also for metal oxides. Using the oxidative dehydrogenation of butane to 1, 3-butadiene as a model reaction, we synthesised and tested 15 bimetallic mixed oxides supported on alumina. We then built a descriptor model for these oxides, and projected the model's results on a set of 1711 mixed oxide catalysts in silico . Based on the model's predictions, six new bimetallic oxides were then synthesised and tested. Experimental validation showed impressive results, with Q 2 > 0.9, demonstrating the power of these low-cost predictive models. Importantly, no interaction terms were included in the model, showing that even if we think that bimetallic oxide catalysts are highly complex materials, their performance can be predicted using simplistic models. The implications of these findings to catalyst optimisation practices in academia and industry are discussed.